Pretreatment of kaempferol-3-O-rutinoside protects H9c2 cells against LPS-induced inflammation through the AMPK/SIRT1 pathway - Ma, Yao-yao; Zhao, Xiao-ni; Zhou, Lan; Li, Sheng-nan; Bai, Juan; Shi, Ling-li; Hua, Fang; Zhou, Peng (Italian Journal of Food Science, 2023)
Kaempferol-3-O-rutinoside (KR) is a flavonoid glycoside derived from traditional Chinese medicine, plants, and tea, and has good myocardial protection. This study focuses on the mechanism of myocardial protection with KR and whether myocardial protection can be achieved by activating the adenosine monophosphate-activated protein kinase–silent mating-type information regulation 2 homolog 1 (sirtuin) (AMPK/SIRT1) signal pathway. Molecular docking technique was used to predict the binding affinity of KR to AMPK. The inflammatory injury model of H9c2 cells was established by lipopolysaccharide (LPS) induction. H9c2 cell proliferation was detected by cell counting kit -8 assay. The apoptosis rate was measured by flow cytometry. Levels of interlukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α) were determined by enzyme-linked-immunosorbent serologic assay. AMPK and SIRT1 expression levels were quantified through reverse transcription-polymerase chain reaction and Western blotting assay. Results indicated that KR has a certain binding affinity with AMPK. KR could increase the growth of H9c2 inhibited by LPS, reduce apoptosis rate, and reverse the elevated levels of IL-1β, IL-6, and TNF-α. Furthermore, KR could suppress the expression levels of AMPK and SIRT1, and AMPK-specific inhibitor (Compound C) could significantly counteract the activation of KR, indicating that its anti-inflammatory effect is achieved by regulating the AMPK/SIRT1 signaling pathway.